Nitric oxide yield from combustion of a low calorific gasification product gas: numerical and experimental study. (12th June 2006) - Brink, Anders; Hupa, Mikko; Kurkela, Esa; Suomalainen, Marjut
The nitrogen oxide yield in a combustor burning an ammonia rich product gas from a bubbling bed gasifier has been investigated. The measurements showed a surprisingly small effect of the excess air in the combustor on the NOx emissions. To understand the reason for this behaviour the nitrogen chemistry in the combustor has been studied using CFD combined with a detailed description of the fuel-N chemistry. With higher oxygen excess a NOx yield of 22% is calculated compared to a measured NOx yield of 21%. In the case with lower oxygen excess the corresponding numbers are 20% and 18%, respectively.